(untitled) (African Disability Rights Yearbook, 2021)
No fewer than 25 African countries have been identified where attacks on and killings of persons with albinism have in recent years been perpetrated. These attacks and killings raise multiple human rights questions. The communication of X v United Republic of Tanzania decided by the Committee on the Rights of Persons with Disabilities concerned a complaint by a person with albinism, who was attacked. Issues such as ratione materia; remedies; legal aid; delays in solving cases; being equal before and under the law, and equal and effective legal protection of the law; torture and re-victimisation; as well as protection of the integrity of the person are the thematic issues covered in the article. In conclusion, the implications of the Mr X decision and how it should reverberate beyond the borders of Tanzania are addressed.